2016
DOI: 10.1186/s12864-016-3360-4
|View full text |Cite
|
Sign up to set email alerts
|

Dhurrin metabolism in the developing grain of Sorghum bicolor (L.) Moench investigated by metabolite profiling and novel clustering analyses of time-resolved transcriptomic data

Abstract: BackgroundThe important cereal crop Sorghum bicolor (L.) Moench biosynthesize and accumulate the defensive compound dhurrin during development. Previous work has suggested multiple roles for the compound including a function as nitrogen storage/buffer. Crucial for this function is the endogenous turnover of dhurrin for which putative pathways have been suggested but not confirmed.ResultsIn this study, the biosynthesis and endogenous turnover of dhurrin in the developing sorghum grain was studied by metabolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 97 publications
5
82
0
3
Order By: Relevance
“…This could potentially mobilise additional nitrogen resources leading to improved growth, particularly at low nitrogen treatments, and is consistent with our observations. This is supported by the results from the analysis of the developing sorghum grain, which showed that although the mature grain is acyanogenic, dhurrin levels are quite high in the immature grains (Nielsen et al 2016). Concomitant with this decrease in dhurrin is an increase in NIT4A and NIT4B2 expression, indicating that the endogenous turnover pathway operates in the seed to provide an alternative nitrogen source for seed storage protein production (Nielsen et al 2016).…”
Section: Molecular Regulation Of Dhurrin and N Turnover Is Complexmentioning
confidence: 74%
See 2 more Smart Citations
“…This could potentially mobilise additional nitrogen resources leading to improved growth, particularly at low nitrogen treatments, and is consistent with our observations. This is supported by the results from the analysis of the developing sorghum grain, which showed that although the mature grain is acyanogenic, dhurrin levels are quite high in the immature grains (Nielsen et al 2016). Concomitant with this decrease in dhurrin is an increase in NIT4A and NIT4B2 expression, indicating that the endogenous turnover pathway operates in the seed to provide an alternative nitrogen source for seed storage protein production (Nielsen et al 2016).…”
Section: Molecular Regulation Of Dhurrin and N Turnover Is Complexmentioning
confidence: 74%
“…Dhurrin synthesis has been shown to be transcriptionally regulated in seedlings (Busk and Møller 2002) and the developing grain (Nielsen et al 2016). Here, CYP79A1 transcript levels were very low in the leaf and root tissue of plants at the three-and five-leaf stage, even when HCNp was quite high.…”
Section: Molecular Regulation Of Dhurrin and N Turnover Is Complexmentioning
confidence: 86%
See 1 more Smart Citation
“…This is evidenced by the increase in significance of the dhurrin–glucose relationships ( r = 0.41 in the control to r = 0.61 in the preflowering treatment block) under preflowering water deficit. It has been proven that under environmental variations, dhurrin can be catabolized to release HCN through the cyanogenesis pathway (Morant et al, 2008) or turned over, thus releasing glucose and ammonia as byproducts through the alternate putative pathway (Adewusi, 1990; Piotrowski et al, 2001; Busk and Møller, 2002; Nielsen et al, 2016). As stress prolongs, the relationships between dhurrin and the sugars decrease in significance, suggesting a complete slowdown of leaf metabolic processes as the plant becomes less reliant on the leaves and more on the remobilization of its stored stem assimilates for its developmental processes.…”
Section: Discusionmentioning
confidence: 99%
“…Most characterization studies in Macadamia and other plants only involved analysis of cyanogenic glycosides using time-consuming assays coupled with HPLC analysis [6,25,26]. Furthermore, typical analysis of releasable cyanide uses tedious assays and subsequent spectrophotometry or LC-or GC-MS analysis [14,27,28]. In this study, hydrogen cyanide was measured directly above the headspace of the different parts of the Macadamia plant including the flowers, leaves, husks, and nuts using selected ion flow tube-mass spectrometry (SIFT-MS).…”
Section: Introductionmentioning
confidence: 99%